Metode-Metode Pendidikan Islam Bagi Anak Usia Dini (THUFULA, 2014)
Man is a creature of God; This is one of the nature of human beings.Another is that the nature of human beings is creatures whose developmentis influenced by the nature and the environment. A human being is veryinteresting. Therefore, he has been the target of studies since past, present,and future. Almost all higher education institutions assess the human, andthe impact of his work on his own, community and environment. One of theaims of man created by God is to be His vicegerent on earth. Therefore, peopleshould be educated from an early age even while still in his mother’s womb.Early childhood is a group of children who are in the process of growth anddevelopment that is unique, in the sense of having a pattern of growth anddevelopment, intelligence, social, emotional, language and communicationin accordance with the rate of growth and development of children. Theimportance of childhood and early childhood characteristics, demandingapproach to be used in learning activities that will be used in the learningactivities that focus on children. At the time of this early age, children need to beeducated as well as possible, with methods appropriate to their circumstances.The educational methods that can be applied are such as, advice, stories, andcustoms. No “bad” or ‘good’method. Because it highly depends on many factors.The important thing taken into account teachers to set a method is knowingthe limits of goodness and weakness methods that will be used, thus allowingit to formulate conclusions about the results/achievement of the objectives ofthe decision.